Dydaktyczne problemy współdziałania w zakresie przeżycia literackiego, zdobywania wiedzy i kształtowania przekonań w nauczaniu literatury = Didactic Problems of Co-Operation in the Field of Literary Experience, Attainment of Erudition and Formation of Convictions in Teaching Literature - Dittmann, Gerhart (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author motivates in his paper, that the essential condition for an efficiency in teaching literature is the dialectic connexion of aesthetic experience, attainment of erudition and formation of convictions. In the process of perception of a piece of literary work the reader's whole personality is engaged and the aesthetic experience is a creative act.
Keywords: dydaktyka literatury